2013
DOI: 10.1124/jpet.112.200691
|View full text |Cite
|
Sign up to set email alerts
|

Cynomolgus Monkey as a Potential Model to Assess Drug Interactions Involving Hepatic Organic Anion Transporting Polypeptides: In Vitro, In Vivo, and In Vitro-to-In Vivo Extrapolation

Abstract: Organic anion-transporting polypeptides (OATP) 1B1, 1B3, and 2B1 can serve as the loci of drug-drug interactions (DDIs). In the present work, the cynomolgus monkey was evaluated as a potential model for studying OATP-mediated DDIs. Three cynomolgus monkey OATPs (cOATPs), with a high degree of amino acid sequence identity (91.9, 93.5, and 96.6% for OATP1B1, 1B3, and 2B1, respectively) to their human counterparts, were cloned, expressed, and characterized. The cOATPs were stably transfected in human embryonic ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(128 citation statements)
references
References 39 publications
10
116
2
Order By: Relevance
“…Therefore, it was suggested that the relative expression levels of these OATPs in liver are similar between cynomolgus monkeys and humans. In addition, high levels of homology have been reported among gene and amino acid sequences for these OATPs between the species (White et al, 2006;Ebeling et al, 2011;Utoh et al, 2012), and also it has been suggested that these OATPs substrate and inhibitor profiles were similar between the species (White et al, 2006;Maeda and Sugiyama, 2010;Shen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it was suggested that the relative expression levels of these OATPs in liver are similar between cynomolgus monkeys and humans. In addition, high levels of homology have been reported among gene and amino acid sequences for these OATPs between the species (White et al, 2006;Ebeling et al, 2011;Utoh et al, 2012), and also it has been suggested that these OATPs substrate and inhibitor profiles were similar between the species (White et al, 2006;Maeda and Sugiyama, 2010;Shen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of homology among gene and amino acid sequences (.95% and .93%, respectively) have recently been reported for OATP1B1 and OATP1B3 between humans and cynomolgus monkeys (White et al, 2006;Ebeling et al, 2011;Utoh et al, 2012). In in vitro functional characterization studies, it has been suggested that cynomolgus monkey OATP1B1, OATP1B3 substrate and inhibitor profiles were similar to those of humans (White et al, 2006;Maeda and Sugiyama, 2010;Shen et al, 2013). Hence, monkeys may be useful as a preclinical in vivo DDI model involving OATP inhibition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study with a large set of well-characterized, structurally diverse compounds concluded that monkey was superior to dog or/and rat in all the methods tested, presumably because monkey is evolutionarily closest to human (Lombardo et al, 2013b). Both uptake and efflux transporters in monkey have been shown to be more predictive of human than rodents and dogs (Syvänen et al, 2009;Shen et al, 2013). The Øie-Tozer model gave the best prediction compared with the other methods.…”
Section: Predicting Volume Of Distributionmentioning
confidence: 99%
“…All transport experiments were performed manually in a 24-well plate on a thermostatic VWR symphony incubating microplate shaker (VWR, Thorofare, NJ) calibrated at 37°C following the protocol described previously with minor modifications (Shen et al, 2013). In brief, cells grown in 24-well plates were rinsed twice with 1.5 ml of prewarmed HBSS.…”
Section: Assessment Of Transporter Inhibitionmentioning
confidence: 99%